PERSEPSI SISWA SMA TERHADAP MATERI PENDIDIKAN KEWARGANEGARAAN (Satu Studi Penelitian di SMA Negeri 3 Semarang dan SMA Don Bosko Semarang) - Seriti Puti D; Susilo Utomo; Tri Cahyo Utomo (Journal of Politic and Government Studies, 2013)
ABSTRACTPancasila is the Indonesian national identity which becomes orientation of valuesand norm for all the people of Indonesia. Pancasila is a part of Civics Education lessonswhich is compulsory from elementary school to university. By weakening of Pancasilavalues gives a big affect to the behavior of Indonesian. Especially, the young generationof Indonesia looks increasingly becomes anti Pancasila. Based on those conditions, thisstudy aimed to determine the perceptions of senior high school students to the CivicsEducation Material containing principles of Pancasila.This study used descriptive quantitative approach, to describe the phenomenonthat occured and was intended to determine the perceptions of senior high schoolstudents on the Civics Education Material in detail. In collecting the data, the authorused a survey method through the distribution of questionnaires. Sampling method in thisresearch was purposive sampling to determine the number of samples in each school,then random sampling technique in the determination of the individual as a sample orPSU (People Sample Units). So the population selected purposively based on targetsstudents who were more dominant and deemed appropriate in accordance with the themeof the study.The results of this study showed that majority of senior high school students gave apositive perception of the Civics Education Material. Senior high school students couldunderstand what is wrong and what is right. There were not many differences perceptionof the material Civics between girls and boys students. Similarly, it happened betweenSMA 3 Semarang and SMA Don Bosko, both class X and class XI did not show anydifferences in perception. However, students could only receive Citizenship EducationMaterial well in theory. In practice there was less congruence between the students'cognitive and affective.Inexpediency of cognitive and affective among senior high school studentsoccurred because the progress of time factor that was even more out of the Indonesianculture. The inappropriate intercourse and lack of parental supervision of the childcaused the child socially easily get carried away with the wrong intercourse. Therefore,the socialization from teachers and parents to effectively supervise children in school andout of school is needed so that children do not fall into the wrong intercourse and moredamage the morale of the Indonesian nation.Keywords: Perception, Cognitive, Civics Education